#TITLE_ALTERNATIVE# - SANDY AGUNG , GALIH
A free-surface flow on a channel with step bottom is solved numerically by an integral equation method. The flow is assumed to be irrotational, two dimensional, and the pattern of flow is steady. Beside that, the fluid is assumed to be ideal which the characteristics are inviscid and incompressible. The numerical result shows that the step generates a train of waves to the free-surface of fluid. The size of waves is influenced by the flow velocity, the height and slope of the step. The waves are characterized as long wave with ratio amplitude to wavelength of order 10(-2) or smaller.